Pyrosequencing Analysis of the Oral Microflora of Healthy Adults - Keijser, B.J.F.; Zaura, E.; Huse, S.M.; van der Vossen, J.M.B.M.; Schuren, F.H.J.; Montijn, R.C.; ten Cate, J.M.; Crielaard, W. (Journal of dental research, 2008)
A good definition of commensal microflora and an understanding of its relation to health are essential in preventing and combating disease. We hypothesized that the species richness of human oral microflora is underestimated. Saliva and supragingival plaque were sampled from 71 and 98 healthy adults, respectively. Amplicons from the V6 hypervariable region of the small-subunit ribosomal RNA gene were generated by PCR, pooled into saliva and plaque pools, and sequenced by means of the Genome Sequencer 20 system at 454 Life Sciences. Data were evaluated by taxonomic and rarefaction analyses. The 197,600 sequences generated yielded about 29,000 unique sequences, representing 22 taxonomic phyla. Grouping the sequences in operational taxonomic units (6%) yielded 3621 and 6888 species-level phylotypes in saliva and plaque, respectively. This work gives a radically new insight into the diversity of human oral microflora, which, with an estimated number of 19,000 phylotypes, is considerably higher than previously reported.